Academic dishonesty and misconduct in online programs and online exams – an Australian study - E., Smith,; L, Clarke, (IJRDO- Journal of Educational Research, 2017)
Now days an increasing number of universities are offering online degrees. In Australia most universities offer online degrees, however, this study will take a closer look at an organisation which offers the largest selection of online courses. For the purposed of this study the organisation will be referred to as “online degree providers” (ODP). Along with this new method of completing degrees comes new forms of academic dishonesty and misconduct. Academic dishonesty and misconduct among students is not a new phenomenon. According to Rokavski and Levy (2007), cheating in general at universities is growing at a rampant rate. Researchers such as Stack (2015) find that academic dishonesty and misconduct at universities nowadays is even more prevalent than in the past due to technological advances, relatively scarce resources and understaffing at universities (Treviño and Butterflied, 1999; Maslen, 2003; Stack, 2015). The most common and widely used notion of academic dishonesty and misconduct at universities is copying and/or cheating on an exam (Teixeira and Rocha, 2010). Hence, these global findings also apply to Australian universities. Therefore, this paper examines academic dishonesty in relation to online exams in Australia. Even though this paper considers academic dishonesty broadly, the focus of the paper is on cheating in online exams. This paper contributes to the limited research literature on academic dishonesty and misconduct in online programs and online exams at Australian universities by taking a close look at what academic dishonesty and misconduct is and how it may be minimised.